The Features of Logistics Flows Formation in Terms of E-commerce - Yevhen Krykavskyy; Nazar Fihun (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
This paper is about the role of media in shaping the logistics flows of the company in terms of ecommerce. It identifies the main trends in logistics and the role of marketing in the competition, and depicts the peculiarities of five forces that have impacts on the enterprise profit. The paper also highlights the main differences between classical and reverse logistics, analysis the role of innovation in the logistics of automotive industry, and depicts the duration structure of the vehicle life cycle from the suppliers of raw materials to the final consumer. It forms the hierarchical structure of the implementation of the logistics system objectives with allocation of conflict of interest place, and analysis the state of the world and in particular European automotive market. Finally, the paper discusses the typical features of automotive consumer’s behavior on the Internet and considered the profile of consumers for the purpose of forming more effective marketing campaigns